The Influence Of Price And Quality Of Kopi Borong On The Purchase Decision At CV Bekat Asia Sinjai Borong - Misna; Haedar Akib; Andi Aslinda; Maya Kasmita; Nurhasnni Muis (Fakultas Ilmu Sosial dan Hukum, 2024)
This study aims to determine how the price and quality of the product Kopi Borong influence purchasing decisions at CV Berkat Asia Sinjai Borong. Respondents in this study are consumers who have purchased Kopi Borong products from CV Berkat Asia who are domiciled in Sinjai Borong District with a total sample of 130 respondents. The sampling technique used the Accidental Sampling technique with data collection using a questionnaire. The data obtained were processed using SPSS 26 which consisted of multiple regression analysis which was first tested using validity tests, reliability tests, and normality tests. The results showed that the price variable had a significant effect on purchasing decisions with a value of Tcount 6,490 > Ttable 1,978 with a significance value of 0.000 <0.05, Product quality had a significant effect on purchasing decisions with a value of Tcount 11.373 > Ttable 1.978 with a significance value of 0.000 < 0.05, and there is a simultaneous effect of price and product quality on the purchasing decision of Kopi Borong products at CV Berkat Asia Sinjai Borong with Fcount 174,013 > Ftable 3,07. The value of the coefficient of determination (Adjusted R2) obtained is 0.728, this means that purchasing decisions are influenced by price and product quality as much as 72.8% while the rest is influenced by other factors.